MENUNTASKAN HASIL BELAJAR MAHASISWA PRODI PENDIDIKAN KIMIA FKIP UNIVERSITAS RIAU DALAM MATA KULIAH KIMIA DASAR II MELALUI PEMBELAJARAN BERDASARKAN MASALAH TAHUN AKADEMIS 2011/2012 - Rasmiwetti '; Miharty '; Rini ' (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Riau (UNRI), 2016)
Basic Chemistry II course is a repetition and development of chemistry which have been learned by students in high school. Therefore, the learning outcomes of student at the course Basic Chemistry II was expected in the high category. Through observations and interviews with students was obtained information that most of the students was difficult to understand about the material. It is necessary to increase the quality of learning in order to better and complete student results through class action research by applying problem-based learning. This class action research aims to improve and complete the learning ability of students of study program of Chemical Education FKIP Riau University academic year 2011/2012 in the course of Basic Chemistry II. This study was conducted in three cycles. The increasing of mastery learning outcomes of students from the cycle I to Cycle II was 25% and from Cycle II to Cycle III was 54.17%. Improving the ability of students to learn this by: 1) Teaching takes place in groups of 5 or 6 people. 2) Using instructional media in the form of textbooks, learning2materials and Student Work Sheet. 3) Lecturers encourage student to be active when group activities. 4) Lecturers provide guidance in groups and classical. 5) Time for classical discussion was long.Keywords : Basic Chemistry II, Problem-based learning, Mastery learning outcomes.